Sinestesia e construção do sentido na Música Popular Brasileira - Paula, Juliana da Silva de (2015)
In this work, we analyze synaesthetic evocations in lyrics of songs from Brazilian Folk Music. We started from the hypothesis that along with the current technological advancements and the confluence of media, we confront ourselves with syncretic feelings which can be surprised, under synaesthetic effects, on the discourse of the songs. The corpus of the research is constituted of the analysis of six lyrics from songs that, in their composition, evoke a mixture of the senses (sound, sight, touch, smell and taste). The theoretical reference involves conceptual definitions about what synaesthesia is and distinguishes this fenomenon from synaesthetic evocations, this one concerning language and poetry, while synaesthesia itself is closer to scientific questions and evidences. The authors used to treat synaesthesia were Simon Baron Cohen and John Harrison, Sérgio Roclaw Basbaum and Antônio Roberto Chiachiri Filho. Regarding the caracteristics and peculiarities of musical language, we used contributions from authors as Oliver Sacks, Murray Schafer and Jota Moraes. To treat the semiotic issues in the analyses of the songs, we count on the authors Lucia Santaella and Luiz Tatit, among others. The textual analyses were concieved under the Peircean semiotic concept, more especifically through the categories of firstness, secondness and thirdness and through trichotomy representamen, object and interpretant. More than classfications, we understand the lyrics of theses songs through meaning relations that emanate from the inner of verbal aspects and poetics, and, therefore, we mainly kept on those constructions that produce synaesthetic evocations, in other words, the ones that bring to memory the presence of feelings to compose a wide range of significations. Under the light of these significations, the analyses are based on the construction of interpretations that also value the global sense through observation of specific elements (concerning the five senses) and also the song as a whole, capable of communicating and conducting to the most miscellaneous sensible experiences